Assessing the Environmental Footprint Reduction of Greener Healthcare: Innovative Life-Cycle Analysis of Ecologically Sustainable Pharmaceuticals in Low-Resource Settings - Inna Noor Inayati; Siti Yuriah; Syed Asif Ali (International Forum of Researchers and Lecturers, 2024)
Eco-pharmaceuticals are an emerging solution in the pharmaceutical industry, aimed at reducing environmental impacts through sustainable production, distribution, and disposal practices. The growing concern over pharmaceutical waste, especially in low-resource settings, highlights the need for greener alternatives. Pharmaceutical residues, often not fully removed during conventional wastewater treatments, contribute significantly to water pollution and disrupt aquatic ecosystems. Eco-pharmaceuticals address these issues by using biodegradable materials, environmentally friendly production methods, and safer disposal techniques, thereby reducing the persistence of pharmaceutical contaminants in the environment. Life-Cycle Assessment (LCA) is an essential methodology used to evaluate the environmental impact of pharmaceutical products, considering all stages from raw material extraction to end-of-life disposal. The results of LCA show that eco-pharmaceuticals significantly reduce water pollution potential and carbon emissions when compared to conventional drugs. Additionally, they offer a more resource-efficient alternative by minimizing waste generation during production and ensuring safer end-of-life disposal. Despite the clear environmental benefits, challenges remain in transitioning to eco-pharmaceuticals, particularly in low-resource settings where infrastructure for waste management is limited. Cost and availability of eco-pharmaceuticals may also pose barriers to widespread adoption. However, with appropriate policy interventions, public education, and technological innovations, these challenges can be addressed. This study underscores the potential of eco-pharmaceuticals in mitigating environmental degradation while offering a sustainable and cost-effective alternative to traditional pharmaceuticals, particularly in regions most vulnerable to pollution.